2021
DOI: 10.1371/journal.pone.0251888
|View full text |Cite|
|
Sign up to set email alerts
|

The smoking paradox in ischemic stroke patients treated with intra-arterial thrombolysis in combination with mechanical thrombectomy–VISTA-Endovascular

Abstract: Background The smoking-paradox of a better outcome in ischemic stroke patients who smoke may be due to increased efficacy of thrombolysis. We investigated the effect of smoking on outcome following endovascular therapy (EVT) with mechanical thrombectomy alone versus in combination with intra-arterial (IA-) thrombolysis. Methods The primary endpoint was defined by three-month modified Rankin Scale (mRS). We performed a generalized linear model and reported relative risks (RR) for smoking (adjustment for age, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In the analysis of the relationship between pre‐stroke aspirin use and infarct volume, WMH volume was included as a covariate in the augmented IPW analysis to explore the association between pre‐stroke aspirin use and infarct volume independently of WMH burden, which has been shown to associate with larger infarct volume 35 and more frequent infarct growth 36 . For hemorrhagic transformation, early neurological deterioration, and favorable 3‐month outcome, adjusted odds ratios (95% confidence interval [CI]) of pre‐stroke aspirin use (vs nonuse) were also estimated by using multivariable logistic regression analysis in the inverse probability weighted data with adjustment for the covariates that were used for the augmented IPW 28–34 . As a priori subgroup analyses, effect modification by stroke subtypes was assessed using multiple linear regression analysis (for infarct volume) or multivariable logistic regression analysis (for hemorrhagic transformation, early neurological deterioration, and favorable 3‐month outcome) in the inverse probability weighted data, with adjustment for the covariates that were used for the IPW.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the analysis of the relationship between pre‐stroke aspirin use and infarct volume, WMH volume was included as a covariate in the augmented IPW analysis to explore the association between pre‐stroke aspirin use and infarct volume independently of WMH burden, which has been shown to associate with larger infarct volume 35 and more frequent infarct growth 36 . For hemorrhagic transformation, early neurological deterioration, and favorable 3‐month outcome, adjusted odds ratios (95% confidence interval [CI]) of pre‐stroke aspirin use (vs nonuse) were also estimated by using multivariable logistic regression analysis in the inverse probability weighted data with adjustment for the covariates that were used for the augmented IPW 28–34 . As a priori subgroup analyses, effect modification by stroke subtypes was assessed using multiple linear regression analysis (for infarct volume) or multivariable logistic regression analysis (for hemorrhagic transformation, early neurological deterioration, and favorable 3‐month outcome) in the inverse probability weighted data, with adjustment for the covariates that were used for the IPW.…”
Section: Methodsmentioning
confidence: 99%
“…In the inverse probability weighted data, potential outcome means 27 of aspirin users and nonusers and subsequently intergroup differences were estimated for (1) infarct volume, (2) the incidence of hemorrhagic transformation, (3) the incidence of early neurological deterioration, and (4) the proportion of favorable functional outcome at 3 months (mRS scores 0–2) by using the teffects aipw function in STATA software to perform augmented IPW: a “doubly robust” method 27 combining IPW with outcome regression. In the outcome regression of the augmented IPW, predefined variables that have been reported to be associated with infarct volume or stroke outcomes 28 , 29 , 30 , 31 , 32 , 33 , 34 were used. In the analysis of the relationship between pre‐stroke aspirin use and infarct volume, WMH volume was included as a covariate in the augmented IPW analysis to explore the association between pre‐stroke aspirin use and infarct volume independently of WMH burden, which has been shown to associate with larger infarct volume 35 and more frequent infarct growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This data suggests that a pharmacoinvasive strategy is suitable for the treatment of current smokers who develop STEMI in rural areas and cannot be transferred to primary PCI centers within 120 min, as recommended in the guidelines. This aggressive beneficial approach was supported by the recent publication of the smoking paradox in patients with ischemic stroke who were treated with intra-arterial thrombolysis in combination with mechanical thrombectomy ( 29 ).…”
Section: Discussionmentioning
confidence: 98%
“…Although tobacco use increases the risk of ischemic stroke, some studies have demonstrated a paradoxical association between current smoking and favorable stroke outcome following intravenous thrombolysis with r-tPA or endovascular treatment (Ovbiagele and Saver 2005;Ali et al, 2013;Kufner et al, 2013;Kvistad et al, 2014;Hussein et al, 2017;Kufner et al, 2021). Studies of this smoking-thrombolysis paradox have shown that TS use is associated with reduced infarct growth, as well as a higher rate of recanalization and reperfusion in TS users treated with IV r-tPA, following ischemic stroke (Kufner et al, 2013).…”
Section: Blood Clotting Thrombus Formation and Use Of Thrombolytics I...mentioning
confidence: 99%